Experimental Evaluation of the Density Ratio Effects on the Cooling Performance of a Combined Slot/Effusion Combustor Cooling System. (30th May 2013) - Andreini, Antonio; Caciolli, Gianluca; Facchini, Bruno; Tarchi, Lorenzo
Abstract : The purpose of this study is to investigate the effects of coolant-to-mainstream density ratio on a real engine cooling scheme of a combustor liner composed of a slot injection and an effusion array with a central dilution hole. Measurements of heat transfer coefficient and adiabatic effectiveness were performed by means of steady-state thermochromic liquid crystals technique; experimental results were used to estimate, through a 1D thermal procedure, the Net Heat Flux Reduction and the overall effectiveness in realistic engine working conditions. To reproduce a representative value of combustor coolant-to-mainstream density ratio, tests were carried out feeding the cooling system with carbon dioxide, while air was used in the main channel; to highlight the effects of density ratio, tests were replicated using air both as coolant and as mainstream and results were compared. Experiments were carried out imposing values of effusion blowing and velocity ratios within a range of typical modern engine working conditions. Results point out the influence of density ratio on film cooling performance, suggesting that velocity ratio is the driving parameter for the heat transfer phenomena; on the other hand, the adiabatic effectiveness is less sensitive to the cooling flow parameters, especially at the higher blowing/velocity ratios.